Quality improvement and practice-based research in neurology using the electronic medical record. Issue 5 (October 2015) - Maraganore, Demetrius M.; Frigerio, Roberta; Kazmi, Nazia; Meyers, Steven L.; Sefa, Meredith; Walters, Shaun A.; Silverstein, Jonathan C.
Abstract : Abstract: We describe quality improvement and practice-based research using the electronic medical record (EMR) in a community health system–based department of neurology. Our care transformation initiative targets 10 neurologic disorders (brain tumors, epilepsy, migraine, memory disorders, mild traumatic brain injury, multiple sclerosis, neuropathy, Parkinson disease, restless legs syndrome, and stroke) and brain health (risk assessments and interventions to prevent Alzheimer disease and related disorders in targeted populations). Our informatics methods include building and implementing structured clinical documentation support tools in the EMR; electronic data capture; enrollment, data quality, and descriptive reports; quality improvement projects; clinical decision support tools; subgroup-based adaptive assignments and pragmatic trials; and DNA biobanking. We are sharing EMR tools and deidentified data with other departments toward the creation of a Neurology Practice-Based Research Network. We discuss practical points to assist other clinical practices to make quality improvements and practice-based research in neurology using the EMR a reality.